2014
DOI: 10.1016/j.eats.2013.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Resection of a Talocalcaneal Coalition Using a Posteromedial Approach

Abstract: Resection is a standard surgical procedure for a talocalcaneal coalition (TCC). A posterior approach is the representative technique for hindfoot endoscopy, and there is only 1 report of endoscopic resection of TCC using this approach. Disadvantages of the posterior approach for TCC are as follows: (1) the indication is limited to posterior-facet coalition, (2) the flexor hallucis longus can be an obstacle in approaching the coalition, (3) the acute insertion angle between the endoscope and instrument reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
3
1
Order By: Relevance
“…Contrary to the literature that suggests the de facto approach to resection usually follows a trial of conservative management [8], the majority of patients in our cohort did not have a trial of conservative management prior to the resection of the coalition. In general, there was minimal benefit for patients that underwent a trial of conservative management when compared with patients who did not.…”
Section: Prior Conservative Management and Additional Operative Inter...contrasting
confidence: 85%
See 1 more Smart Citation
“…Contrary to the literature that suggests the de facto approach to resection usually follows a trial of conservative management [8], the majority of patients in our cohort did not have a trial of conservative management prior to the resection of the coalition. In general, there was minimal benefit for patients that underwent a trial of conservative management when compared with patients who did not.…”
Section: Prior Conservative Management and Additional Operative Inter...contrasting
confidence: 85%
“…It did not seem the case that a trial of conservative treatment in surgically managed coalitions led to a substantial improvement in AOFAS scores when compared with surgical resection alone. This is interesting as it suggests that the mainstay of management, a trial of conservative treatment before resection, may not influence the overall outcome for the patient [ 8 ]. However, the benefits of conservative intervention may not be immediately clear from this study.…”
Section: Reviewmentioning
confidence: 99%
“…The surgical technique was similar to Bonasia et al 3 and Hayashi et al 8 in utilizing prone positioning and 2 working peri-Achilles tendon portals. The FHL and neurovascular bundle were protected medial to the burr using a retractor (Figure 2C), although the distraction was not needed in the surgery.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Moreover, the posterior subtalar articular facet can be fully exposed, and the extent of excision can be evaluated by arthroscopy. Hayashi et al 8 reported a surgical technique of resecting the middle and posterior articular facets using a posteromedial approach. They found that arthroscopy allowed a sufficient working space and could be a direct approach to the middle and posterior articular facets without obstruction.…”
Section: Introductionmentioning
confidence: 99%